Bovine TLR2 and TLR4 mediate Cryptosporidium parvum recognition in bovine intestinal epithelial cells. (August 2015) - Yang, Zhengtao; Fu, Yunhe; Gong, Pengtao; Zheng, Jingtong; Liu, Li; Yu, Yuqiang; Li, Jianhua; Li, He; Yang, Ju; Zhang, Xichen
Abstract: Cryptosporidium parvum ( C . parvum ) is an intestinal parasite that causes diarrhea in neonatal calves. It results in significant morbidity of neonatal calves and economic losses for producers worldwide. Innate resistance against C . parvum is thought to depend on engagement of pattern recognition receptors. However, the role of innate responses to C . parvum has not been elucidated in bovine. The aim of this study was to evaluate the role of TLRs in host-cell responses during C . parvum infection of cultured bovine intestinal epithelial cells. The expressions of TLRs in bovine intestinal epithelial cells were detected by qRT-PCR. To determine which, if any, TLRs may play a role in the response of bovine intestinal epithelial cells to C . parvum, the cells were stimulated with C . parvum and the expression of TLRs were tested by qRT-PCR. The expression of NF-κB was detected by western blotting. Further analyses were carried out in bovine TLRs transfected HEK293 cells and by TLRs-DN transfected bovine intestinal epithelial cells. The results showed that bovine intestinal epithelial cells expressed all known TLRs. The expression of TLR2 and TLR4 were up-regulated when bovine intestinal epithelial cells were treated with C . parvum . Meanwhile, C . parvum induced IL-8 production in TLR2 or TLR4/MD-2 transfected HEK293 cells. Moreover, C . parvum induced NF-κB activation and cytokine expression in bovine intestinal epithelial cells. The induction of NF-κB activation and cytokine expression by C . parvum were reduced in TLR2-DN and TLR4-DN transfected cells. The results showed that bovine intestinal epithelial cells expressed all known TLRs, and bovine intestinal epithelial cells recognized and responded to C . parvum via TLR2 and TLR4.